prohibition of reprisals to repel international aggression - nadhem saadoon, Dr. Osama (Basra studies journal, 2022)
Reprisals are pressure procedures detract the provision of international laws. A state shall respond to illegal actions committed by other country , aiming at deter it by extrajudicial means or in respond to an attack or assault. In spite of cruelty of these attacks that have been prohibited and arranged its responsibility by international law , however it not a justification to face it by violence means vengeance to the attack that the state have been faced , So the reprisals considered prohibited on the international custom and the general international law and human international law considered as illegal acts according to charter of United states. The international law is rooting in prohibition of reprisals of aggression is to protect the security of the international community and keep in safe, so what the international law want is to keep the security international.